ANALISIS KOMPARATIF PEMIKIRAN FILSAFAT POLITIK AL-FARABI DAN PLATON - Richo Bintang Mahendra (UIN Sunan Kalijaga Yogyakarta, 2020)
This article describes about the original dimensions of al-Farabi's Islamic political philosophy by comparing it with Plato's political philosophy. The originality of philosophical thought in Islam was questioned critically by the orientalists. Orientalists had claimed that Islamic philosophy is simply a diversion from Greek philosophy. However, Islamic philosophy is an elaboration of classical Greek philosophical thought. In the hands of Muslim philosophers, Greek philosophical thought reached perfection. So that it cannot be said that Islamic philosophical thought is only diversion of Greek philosophy. This elaboration effort appears in the thought of Al-Farabi's political philosophy which is considered very Platonnic. In this case, there are fundamental differences between Platon's political philosophical thought and the political philosophy thought was built by Al-Farabi. The difference lies in their analysis of the ideal leader, the goals of the state, and the classification efforts of good and bad governance political regimes. Through these differences, it can be seen that Al-Farabi's political philosophy has its own characteristics, that is a combination of faith and philosophy.